Building better teams 70 tools and techniques for strengthening performance within and across teams - Barner, Robert (Robert W.); Barner, Charlotte P., 1957-; ProQuest (Firm) (San Francisco : Pfeiffer, 2012)
"Over the past 10 years in the field of human and organizational development, the approach to team building has moved from problem solving and conflict management to helping work groups and organizations build a foundation of trust, cooperation, and mutual support. Focusing on collaboration rather than resolving conflict, Creating Collaboration: Tools for Building and Strengthening Team and Organizational Performance offers at fresh approach to team building. It provides proven tools for the most common challenges faced by groups, including establishing trust, gaining goal alignment, building consensus, working virtually and across boundaries, and dealing with setbacks"--
Machine generated contents note: List of Tools List of Figures and Tables Acknowledgments About the Authors About the Contributors Introduction SECTION ONE A Systematic Approach to Team Building Chapter 1 Getting Started Chapter 2 Planning the Team-Building Session Chapter 3 Implementation, Action Planning, and Follow-Up Chapter 4 Selecting the Right Team-Building Tools SECTION TWO Managing Team-Building Challenges Chapter 5 Clarifying Future Direction Chapter 6 Fostering Team Innovation Chapter 7 Establishing Mutual Trust and Collaboration Chapter 8 Managing Change Chapter 9 Building Commitment Chapter 10 Managing Organizational Boundaries Chapter 11 Working Virtually Chapter 12 Overcoming Setbacks Chapter 13 Managing Across Cultures SECTION THREE Tools and Techniques for Team Building Chapter 14 The Tool Kit Index.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Teams in the workplace; Personnel management; Performance standards; Electronic books